Nomenclatural corrections in Aizoon subg. Namibiana (Aizooideae: Aizoaceae) - Klak, Cornelia; Bruyns, Peter V. (Phytotaxa, 2018)
The recent study by Klak et al. (2017) showed that the species of the genera Galenia Linnaeus (1753: 359), and Plinthus Fenzl (1839: 51) should be referred to Aizoon Linnaeus (1753: 488) (Aizooideae Spreng. ex Arn., Aizoaceae Martinov). In its new circumscription, Aizoon is recognized by capsules with reduced expanding tissue, and leaves and/or stems covered by silvery hairs or hair-like to rounded papillae (see Klak et al., 2017).